Ray tracing in Mac OS X - Lim, Bing Yan (2014)
This project is a feasibility study on programming of computer graphics on the Apple computer, particularly in ray-tracing. The aim of the project is also to create a working port of the popular ray-tracing application, POV-Ray for the Apple Computers. The project takes into consideration that one of the main focus of the project is to create an application that is not only able to perform the functions that the POV-Ray for Windows program is capable of, but also to retain, as much as possible, the layout and aesthetics of the original graphical user interface elements.